A new demotic translation of (excerpts of) a chapter of the Book of the Dead - Quack, Joachim Friedrich (The journal of Egyptian archaeology, 2014)
The funerary papyrus BN 149 has long been known to contain mainly a Demotic translation of the Book of the Dead, chapter 125. Recently, its first section was identified as a translation of a composition otherwise sometimes associated with the so-called 'Book of Traversing Eternity'. Still, the description of a vignette and a short text inserted into chapter 125 have, up to now, defied identification. It is shown here that the latter is a Demotic translation of chapter 128 of the Book of the Dead, with substantial omissions, which are probably the work of a redactor who wished to fit the composition better to funerary usage. Furthermore, the vignette being described is the one belonging to chapter 148 of the Book of the Dead. Some special points concerning the translation of classical Egyptian words and verbal forms are discussed. تحتوى البردية الجنائزية BN 149 على ترجمة ديموطيقية لكتاب الموتى فصل 125 كما هو معروف من منذ زمن طويل. و اتضح حديثا أن جزئها الأول هو ترجمة لمؤلف يرتبط أحيانا بما يسمى ”كتاب العبور إلى الخلود“. و حتى الآن يصعب تحديد وصمف فقرة و نص قصير أضيف إلى الفصل 125 ، و هو ترجمة ديموطيقية للفصل 128 من كتاب الموتى، مع إغفالات هامة ، و التى ربما تكون
Gesehen am 02.06.2020